Mellein: Production in culture by Macrophomina phaseolina isolates from soybean plants exhibiting symptoms of charcoal rot and its role in pathology - Khambhati, Vivek H.; Abbas, Hamed K.; Sulyok, Michael; Tomaso-Peterson, Maria; Chen, Jian; Shier, Wayne Thomas (Frontiers in Plant Science, 2023)
Macrophomina phaseolina (Mp) is a fungal pathogen proposed to enter host roots by releasing toxins that induce local necrosis in roots allowing entry of hyphae. Mp is reported to produce several potent phytotoxins, including (-)-botryodiplodin and phaseolinone, but isolates that do not produce these phytotoxins retain virulence. One hypothesis explaining these observations is that Mp isolates may possess sufficient genetic variability to allow production of other unidentified phytotoxin(s) responsible for virulence. A previous study of Mp isolates from soybean found 14 previously unreported secondary metabolites, including mellein, which has various biological activities. This study was conducted to investigate the frequency and amounts of mellein produced in culture by Mp isolates from soybean plants exhibiting symptoms of charcoal rot and to investigate the role of mellein in any observed phytotoxicity. LC-MS/MS analysis of cell-free culture filtrates (CCFs) from 89 Mp isolates revealed that 28.1% produced mellein (49–2,203 µg/L). In soybean seedlings in hydroponic culture, Mp CCFs diluted to 25% (vol/vol) in hydroponic growth medium induced phytotoxic symptoms with frequencies of 73% chlorosis, 78% necrosis, 7% wilting, and 16% death, and at 50% (vol/vol) induced phytotoxicity with frequencies of 61% chlorosis, 82% necrosis, 9% wilting, and 26% death. Purified mellein (40–100 µg/mL) in hydroponic culture medium induced wilting. However, mellein concentrations in CCFs exhibited only weak, negative, insignificant correlations with phytotoxicity measures in soybean seedlings, suggesting that mellein does not contribute substantially to observed phytotoxic effects. Further investigation is needed to determine if mellein plays any role in root infection.